Holistic Leadership: Integrating Self-Awareness, Emotional Regulation, and Moral Courage - Liena Prajogi (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2025)
This study examines holistic leadership as an integrative approach that unites self-awareness, emotional regulation, integrity, moral courage, empathy, and humane values in leadership practice. In an era of uncertainty and ethical complexity, leadership effectiveness requires more than technical competence; it demands the alignment of cognitive, emotional, and moral capacities. This research employs a qualitative literature review, analyzing peer-reviewed journals and scholarly books published between 2005 and 2024. Data were examined using thematic analysis to identify the core dimensions of holistic leadership. The findings indicate that holistic leadership emerges from the integration of rational thinking (head), emotional intelligence (heart), and moral integrity (soul). Leaders who balance these dimensions demonstrate higher ethical consistency, psychological safety, trust, and sustainable organizational commitment. Moreover, empathy and love are identified as essential moral forces that strengthen ethical decision-making and humane leadership practices. This study contributes to leadership literature by conceptualizing leadership as a human-centered and morally grounded process with practical implications for leadership development.